2008
DOI: 10.1002/jgm.1180
|View full text |Cite
|
Sign up to set email alerts
|

Adeno‐associated virus‐mediated expression of kallistatin suppresses local and remote hepatocellular carcinomas

Abstract: Intraportal injection of rAAV-kallistatin suppressed hepatic and subcutaneous HCC tumors, relying on its anti-angiogenic and anti-proliferative activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
27
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 42 publications
3
27
0
Order By: Relevance
“…With this system, we demonstrated that intraportal delivery of AAV vectors led to long-term and high-level expression of the transgenes localized to the mouse liver [18,19]. Similar results have been obtained in rats by using this method [20,21].…”
Section: Introductionsupporting
confidence: 84%
“…With this system, we demonstrated that intraportal delivery of AAV vectors led to long-term and high-level expression of the transgenes localized to the mouse liver [18,19]. Similar results have been obtained in rats by using this method [20,21].…”
Section: Introductionsupporting
confidence: 84%
“…(13) But the mechanisms are not clear as kallistatin showed no effect on expression of PCNA, nor the apoptosis-related proteins including Bal-2, Bax, and caspase-3. As caspase-3 is the key 'effector' protease in the apoptotic cascade, the results might suggest that kallistatininduced cell apoptosis may be caspase-independent.…”
Section: Discussionmentioning
confidence: 99%
“…(10,11) We have recently reported that adeno-associated virus-mediated expression of kallistatin inhibited angiogenesis and growth of colon and HCC tumors in mice. (12,13) …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro, the virus could deplete PTTG1 in hepatoma cells, resulting in apoptosis. Furthermore, intratumoural injections of the virus led to inhibition of tumour growth in a xenograft tumour in mice 59 . Another recent study concerns RNAi cancer gene therapy in a mouse model of hepatocellular carcinoma (test-O-MYC; LAP-tTa).…”
Section: Issn: 0975-8232mentioning
confidence: 99%